Epidemiological study of thoracolumbar spine fracture patients reported to tertiary care center of Central India - Ambulgekar, Rajesh Kishanrao; Ghag, Niranjan Sunil (International Journal of Research in Orthopaedics, 2023)
Background: Thoracic and lumbar spine fractures account for 90% of all spine fractures recorded. In low- and middle-income countries, spinal injuries are associated with significant disability and decreased life expectancy. Non-operatively, these injuries can be managed with a thoracolumbar orthosis or hyperextension cast. The operative management with a posterior, anterior or combined approach will offer immediate mobilization and earlier rehabilitation, providing a better environment for restoration of neurological function. Aim of the study was to find out epidemiology of patients with thoracolumbar spine fracture patients. Methods: A cross sectional observational study was conducted in department of orthopaedics at tertiary care, teaching hospital among patients with traumatic thoracolumbar spine fractures. Epidemiological data variables were collected. In statistical analysis data from 60 patient reported was recorded and analysed. Results: Fall from height is the leading mechanism of injury among middle aged people (30-60years) with male predominance, accounting for 58.33 percent of all spinal cord injury cases. The majority (45%) of fractures were of the burst kind, followed by compression (28.3%), and then translation/rotation (21.6%). And the most-rare of all was the distracted type (just 5%). An only 15% of patients had had a complete spinal injury, whereas the remaining 85% had sustained incomplete/ no spinal cord injury. Conclusions: Knowledge about the burden brought on by spinal cord injury makes it clear that preventing such injuries is the backbone of care. preventive measures for high-risk individuals and early definitive response by paramedics can help reducing the load caused by these injuries.